Efektivitas Akreditasi Sekolah sebagai Upaya Meningkatkan Mutu Pendidikan - Halimatus Sakdiyah; Pramudita Retno Palupi; Indah Saputri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Considering that Indonesian education is currently still lagging behind many other countries. Efforts must be made immediately to improve education standards in Indonesia in order to have equal competitiveness with other countries. So that all schools must carry out accreditation as a guarantee of quality. Aims to analyze the role of school accreditation as an effective evaluation tool for improving the quality of education in Indonesia. This research is categorized into literature research which is a series of studies related to library data collection methods through various information. The National Accreditation Board for Madrasah Schools (BAN-SM) is one of the accreditation institutions in Indonesia. In general, the flow of accreditation mechanisms can be implemented through target setting, visitation, validation, verification and determination of results and accreditation certificates. Schools also carry out accreditation follow-up as evaluation material for the development of the school. There are also several challenges and obstacles to accreditation along with solutions that can be taken. Quality assurance of education is very important to ensure quality education as an effort to produce quality human resources. Therefore, it is very important to carry out school accreditation as a strategic step to maintain the quality of education that is evenly distributed throughout the country.